Bluetooth embedded digital ammeter with android app data logging - Chin Fhong Soon; Boon Huei Teng; Kian Sek Tee; Siat Ling Jong; Mohd Khairul Ahmad; Marlia Morsin; Tiong Hin Ong (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Monitoring current supplies to light emitting diode (LED) luminaires is one of the reliability tests performed manually. Bluetooth (HC-05) embedded digital ammeter was proposed to acquire currents of a badge of LED products and hence, quality can be assured. Android App was designed to remotely record the current supplies to the different models of LED products and checking if the current measured is within the allowed range. The current data can be further analysed to control the quality of the LED luminaires produced. The pass and fail-current range can be set in the digital ammeter for alerting abnormal current measured by the operator. Therefore, IOT embedded digital ammeter will help in monitoring data consistency of LED products and improve quality assurance procedure.